Techno-Economic Analysis of Hydraulic Fracturing As A Solution for Developing Low-Resistivity and Low-Quality Zone on Offshore “RI” Field - Chandra, Steven; Herwandi, Ilma Mauldhya (Journal of Earth Energy Engineering, 2021)
Hydrocarbon production in Indonesia is continuously decreasing on a yearly basis, which is in contrast with its increasing level of consumption. Low-quality and low-resistivity reservoir zones are deemed to possess a lot of hydrocarbon potentials, however, little priority has been placed on their development due to their small level of production. The "RI" field that was utilized in this study is a mature offshore field with a reservoir which has a low-quality and low-resistivity zone. This area has been in use for more than thirty years, therefore its rate of oil production has declined. This study aims to review the techno-economic aspects of well stimulation in the form of hydraulic fracturing. And also, to determine the development method that is suitable for low-quality fields. The hydraulic fracturing process was modelled using Fracpro software as input parameters for the reservoir production simulations. The reservoir behavior was simulated using the CMG software to observe the amount of hydrocarbon liable for production in various development scenarios. Three cases were performed on the "RI" field, which was stimulated for ten years of operation. The first case was the instance with the natural flow, while the second implemented hydraulic fracturing at the beginning of production, and the third was the implementation of hydraulic fracturing, which started in the middle of the production period. Then, the three cases are evaluated utilizing a Gross Split scheme, to calculate the economics of the project both from the government and contractor's aspects. The simulation study concluded that fracturing at the beginning of the LRLC zone development is the most profitable. The novelty of this study is the comparison of scenarios for the implementation of hydraulic fracturing methods in fields with low-resistivity and low-quality zone whose economic value is evaluated by the Gross Split scheme.